Fluorescence polarization assays in high-throughput screening and drug discovery: a review - Hall, Matthew D (Methods Appl Fluoresc, 2016)
The sensitivity of Fluorescence Polarization (FP) and Fluorescence Anisotropy (FA) to molecular weight changes has enabled the interrogation of diverse biological mechanisms, ranging from molecular interactions to enzymatic activity. Assays based on FP/FA technology have been widely utilized in high-throughput screening (HTS) and drug discovery due to the homogenous format, robust performance and relative insensitivity to some types of interferences, such as inner filter effects. Advancements in assay design, fluorescent probes, and technology have enabled the application of FP assays to increasingly complex biological processes. Herein we discuss different types of FP/FA assays developed for HTS, with examples to emphasize the diversity of applicable targets. Furthermore, trends in target and fluorophore selection, as well as assay type and format, are examined using annotated HTS assays within the PubChem database. Finally, practical considerations for the successful development and implementation of FP/FA assays for HTS are provided based on experience at our center and examples from the literature, including strategies for flagging interference compounds among a list of hits.